Renal targeting potential of a polymeric drug carrier, poly-L-glutamic acid, in normal and diabetic rats - Chai, H.J.; Kiew, L.V.; Chin, Y.; Norazit, A.; Noor, S.M.; Lo, Y.L.; Looi, C.Y.; Lau, Y.S.; Lim, T.M.; Wong, W.F.; Abdullah, N.A.; Sattar, M.Z.A.; et al. (Dove Medical Press, 2017)
Background and purpose: Poly-l-glutamic acid (PG) has been used widely as a carrier to deliver anticancer chemotherapeutics. This study evaluates PG as a selective renal drug carrier. Experimental approach: 3H-deoxycytidine-labeled PGs (17 or 41 kDa) and 3H-deoxycytidine were administered intravenously to normal rats and streptozotocin-induced diabetic rats. The biodistribution of these compounds was determined over 24 h. Accumulation of PG in normal kidneys was also tracked using 5-(aminoacetamido) fluorescein (fluoresceinyl glycine amide)-labeled PG (PG-AF). To evaluate the potential of PGs in ferrying renal protective anti-oxidative stress compounds, the model drug 4-(2-aminoethyl)benzenesulfonyl fluoride hydrochloride (AEBSF) was conjugated to 41 kDa PG to form PG-AEBSF. PG-AEBSF was then characterized and evaluated for intracellular anti-oxidative stress efficacy (relative to free AEBSF). Results: In the normal rat kidneys, 17 kDa radiolabeled PG (PG-Tr) presents a 7-fold higher, while 41 kDa PG-Tr shows a 15-fold higher renal accumulation than the free radiolabel after 24 h post injection. The accumulation of PG-AF was primarily found in the renal tubular tissues at 2 and 6 h after an intravenous administration. In the diabetic (oxidative stress-induced) kidneys, 41 kDa PG-Tr showed the greatest renal accumulation of 8-fold higher than the free compound 24 h post dose. Meanwhile, the synthesized PG-AEBSF was found to inhibit intracellular nicotinamide adenine dinucleotide phosphate oxidase (a reactive oxygen species generator) at an efficiency that is comparable to that of free AEBSF. This indicates the preservation of the anti-oxidative stress properties of AEBSF in the conjugated state. Conclusion/Implications: The favorable accumulation property of 41 kDa PG in normal and oxidative stress-induced kidneys, along with its capabilities in conserving the pharmacological properties of the conjugated renal protective drugs, supports its role as a potential renal targeting drug carrier.